First-Year students’ experiences of ‘transition as induction’ at a South African University - Fru, Raymond; Botes, Wiets; Felix, Alan; Awung, Felix; Wepener, Tiani; Moloele, Richard (Penerbit Universiti Kebangsaan Malaysia, 2024)
The emergence of the global pandemic has had devastating effects on institutions of higher learning. In South Africa, many universities had to swiftly switch to online teaching and learning in a bid to mitigate the effects of the pandemic without considerable repercussion on the academic project. The paper investigates first-year undergraduate students’ experiences of induction as a critical phase of university transition at a South African university. The focus was to investigate how first-year undergraduate students transition into the unknown university environment as they come from various backgrounds. A case study research design was employed in the study. The population included first-year students across all schools in various areas of specialisation at the South African University. Given this population, a purposive sampling technique was employed in the study from which selected students to the tune of forty were interviewed. The findings revealed that the students had varying experiences of transition. Nuanced with the theory of resilience, these experiences were then interpreted following the constructions of deterioration, adaptation, and recovery. The study serves as valuable feedback on how South African universities can go about transforming their cultures, systems, and policies to better support first-year students during a phase of induction.